2018
DOI: 10.1038/s41598-018-26866-8
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of atlanto-occipital dissociation: Standardised measurements of normal craniocervical relationship in finless porpoises (genus Neophocaena) using postmortem computed tomography

Abstract: Due to the different craniocervical structures in humans and cetaceans, a standardised method assessing the normal craniocervical relationship in cetaceans is lacking, causing difficulties in defining the presence of atlanto-occipital dissociation (AOD) in cetaceans. The present study aimed to 1) describe a novel standardised method of determining the normal craniocervical relationships, and 2) define the 95% accuracy range of the normal craniocervical relationship in finless porpoises (genus Neophocaena), tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 44 publications
(36 reference statements)
0
6
0
Order By: Relevance
“…Virtopsy using postmortem computed tomography (PMCT) and postmortem magnetic resonance (PMMR) imaging (PMMRI) has been implemented in the pioneering virtopsydriven cetacean stranding response program in Hong Kong (HK) waters, to provide vital or additional information for conventional necropsy (Kot et al, 2016(Kot et al, , 2018(Kot et al, , 2019(Kot et al, , 2020Chan et al, 2017;Yuen et al, 2017). Stranded cetacean carcasses found in HK waters are often badly degraded (Jefferson et al, 2002) as high temperature and humidity accelerate autolysis (Klein et al, 2016), hampering stranding response personnel and veterinarians in the documentation of postmortem findings and tissue sampling (Tsui et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Virtopsy using postmortem computed tomography (PMCT) and postmortem magnetic resonance (PMMR) imaging (PMMRI) has been implemented in the pioneering virtopsydriven cetacean stranding response program in Hong Kong (HK) waters, to provide vital or additional information for conventional necropsy (Kot et al, 2016(Kot et al, , 2018(Kot et al, , 2019(Kot et al, , 2020Chan et al, 2017;Yuen et al, 2017). Stranded cetacean carcasses found in HK waters are often badly degraded (Jefferson et al, 2002) as high temperature and humidity accelerate autolysis (Klein et al, 2016), hampering stranding response personnel and veterinarians in the documentation of postmortem findings and tissue sampling (Tsui et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Virtopsy provided numerous unique findings that could supplement and might even partially replace conventional necropsy. In this study, atlanto-occipital dissociation was commonly observed in PMCT of the stranded cetaceans Kot et al, 2018a). Skeletal anomalies, including osteolytic lesions in vertebra suggestive of spondylolysis or spondylolisthesis, physeal plate fractures or misalignment, and intramedullary bone islands, were also noted in some cases (Kot et al, 2016).…”
Section: Resultsmentioning
confidence: 58%
“…PMMRI was performed with a GE SIGNA Explorer 1.5 Tesla MR scanner (General Electric Company, Wisconsin, United States) or a 0.25 Tesla Esaote Vet MR Grande scanner (Esaote Biomedica, Genoa, Italy). Details of scanning parameters may refer to previous publications (Kot et al, 2016(Kot et al, , 2018a(Kot et al, , 2019(Kot et al, , 2020aYuen et al, 2017). Datasets were saved in DICOM 3.0 format.…”
Section: Virtopsymentioning
confidence: 99%
See 1 more Smart Citation
“…Like other animals of native, wild or migratory fauna, opossum are protected by the Brazilian environmental crimes law which prohibits killing, persecuting, hunting, catching or using these animals in any other way without a permit or authorization from the competent authority (Brasil, 1998). From this point of view, postmortem computed tomography (PMCT) is a valuable tool for identification and documentation of osteological structures in wild animals (Kot et al, 2018).…”
Section: Introductionmentioning
confidence: 99%